The Physical Activity Transition among Adults in China: 1991–2011 - Ng, Shu Wen (2014)
Previous studies have linked work, home production, travel activities, and inactivity with weight and health outcomes. However, these focused on average physical activity over time rather than changes in physical activity and associated socio-demographic and economic factors and urbanicity. Using the 1991–2011 China Health and Nutrition Survey data, we estimated the metabolic equivalent of task hours per week for individuals in occupational, domestic, travel, and active leisure domains and sedentary hours per week. We present the distributions among adult men and women (aged 18–60) and use quantile regression models to explore factors associated with these trends. Trend analyses on the distribution of physical activity show declines along the whole distribution of occupational physical activity for men and women and domestic physical activity for women in China. These patterns remain consistent after adjusting for individual- and household-level factors. Controlling for urbanicity mitigated the decrease in occupational physical activity, particularly for men, but not the decrease in domestic physical activity. Given China's rapid urbanization and its association with occupational physical activity declines and the strong time trend in domestic physical activity, there is a need to invest in interventions and policies that promote physical activity during leisure and travel times.